Silica Nanowires Reinforced with Poly(vinylidene fluoride‐co‐hexafluoropropylene): Separator for High‐Performance Lithium Batteries. Issue 1 (13th December 2021) - Du, Qingchuan; Shi, Shumin; Zhang, Lida; Yan, Zhongyuan; Zeng, Xu; Wu, Jingjing; Zhou, Weixin; Huang, Zhen‐Dong; Masese, Titus; Ma, Yanwen
Abstract: Separators are key components that physically separate and chemically connect the anode and cathode to guarantee the safety and cycle stability of batteries. Herein, based on the building concept of a bird's nest, we have developed separators comprising SiO2 nanowires reinforced with poly(vinylidene fluoride‐co‐hexafluoropropylene) (PVDF‐HFP). In particular, the hybrid separators with 39% of PVDF‐HFP exhibit much enhanced tensile strength, Young's moduli, flexibility, and elongation as a result of a strong crosslink effect, compared to bare SiO2 nanowire separator, while yet maintaining excellent electrolyte wettability, high ionic conductivity, and wide electrochemical window. Moreover, the hybrid separators also demonstrate excellent thermal stability and dendrite suppression capability. Lithium metal batteries assembled using the hybrid separators with LiFePO4 as the cathode achieve excellent rate performance and cyclic stability. The discharge capacities attained at a current density equivalent to 0.2 C and 2 C rate are 157 and 126 mAh g −1, respectively. A capacity of 99 mAh g −1 is still maintained at 2 C rate after 500 cycles. This study illuminates SiO2 nanowires reinforced with PVDF‐HFP as promising separators for high‐energy, high‐power and safe lithium batteries. Abstract : Based on the building concept of a bird's nest, the mechanical properties of separators comprising SiO2 nanowires have been remarkably reinforced with poly(vinylidene fluoride‐co‐hexafluoropropylene) without obvious degradation of electrochemical performance.